Breast Cancer Prevention Education Through Community Empowerment and TPS (Transactional, Precise, and Skilled) Communication Model in Bontang City - Asbi, Erni Asneli; Siregar, Diyanti Isnani; Zein, Khairu; Triani, Emi; Marpaung, Nicholas (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The prevalence of breast cancer in Indonesia is still increasing. Data from the Global Cancer Observatory shows that the most common cancer case in Indonesia is breast cancer. Meanwhile, the incidence of breast and cervical cancer in Bontang City reaches 30% of the overall cancer data in Bontang (Akurasi.id, 2024). Therefore, there is a need for a health promotion campaign and breast cancer prevention using simple communication methods. This program aimed to provide education to health cadres (PKK) in three sub-districts of Bontang, targeting 100 participants. Five sub-districts were selected from each of the three sub-districts, with seven participants sampled from 10 sub-districts and six participants sampled from ﬁve sub-districts. Participants were selected using purposive sampling. The program employed a participatory research approach based on community empowerment, using the TPS (Transactional, Precise, and Skilled) communication model. The program was conducted in three stages. In the ﬁrst stage, theoretical information related to breast cancer and its prevention was provided, along with 100 questions and answers shared online beforehand. The second stage involved practicing breast self-examination (SADARI). The third stage combined theory and practice, incorporatingeducational strategies through games and evaluations. The program results showed that 83% of participants agreed that knowledge about breast cancer and its prevention was necessary. The program successfully improved the knowledge and attitudes of PKK/health cadres through an interactive, participatory approach. Although there were barriers related to participant agility, support from trained organizers proved eﬀective in overcoming them. These ﬁndings conﬁrm the importance of health education that emphasizes two-way communication and breast cancer prevention.